Discovering genetic variants contributing to sleep dysfunction in presymptomatic Alzheimer's mice: Genetics/genetic factors of Alzheimer's disease. (7th December 2020) - Hadad, Niran; Dunn, Amy R.; O'Connell, Kristen M.S.; Kaczorowski, Catherine C.
Abstract: Background: Disordered sleep is frequently observed in Alzheimer's disease patients. Sleep loss is associated with increased Aβ and tau accumulation in both AD patients and model organisms. Furthermore, cognitively intact individuals with impaired sleep are at higher risk for AD. Although individual differences in sleep are known to be highly heritable, little is known of the genetic factors associated with sleep dysfunction in aging and AD and if these contribute to disease development. Method: Sleep was assessed at a presymptomatic age (6‐7 months) in a panel of genetically diverse mice carrying familial AD mutations, which better models complex etiology of human AD (AD‐BXDs; Neuner et al 2019). Sleep‐wake activity was measured for five consecutive days using the PiezoSleep tracking system across 25 AD‐BXD strains and their nontransgenic littermates (Ntg‐BXD). Result: AD‐BXD mice slept significantly less during the dark cycle compared to Ntg‐BXDs. Additionally, reduction of sleep was observed during the transition from dark to the light cycle, suggesting disruption of circadian function. Females slept less than males regardless of AD mutation status. We identified a significant quantitative trait locus (QTL) on chromosome 9 associated with total sleep, this region is syntenic with a regions on the human chromosome 11, harboring six sleep‐associated human GWAS SNPs, demonstrating the relevance of this region to human biology. Additionally, we identified a QTL for hourly sleep at ZT14 that mapped to intron 1 of the gene Kirrel3 of chromosome 9 (∼20 mb downstream of the sleep‐QTL). Differential gene expression implicates Kirrel3 as a novel target‐gene for validation. Conclusion: We provide the first evidence that genetic factors interact with AD mutations to influence sleep behavior, and identified two regions causally associated with variation in sleep in the AD‐BXDs. Mouse‐to‐human comparison suggest that both region are relevant to humans, demonstrating the value of the AD‐BXDs as a translational AD model. Future work will leverage genome engineering to correct sleep‐associated variants to test the delay or prevention of cognitive deficits onset apparent in the AD‐BXDs by 14 months of age. These studies may identify novel therapeutic targets to treat AD dementia.